(-)-Clausenamide alleviated ER stress and apoptosis induced by OGD/R in primary neuron cultures. (1st September 2020) - Wu, Fei; Zhang, Rumin; Feng, Qizhen; Cheng, Hongju; Xue, Jianjun; Chen, Jing
ABSTRACT: Objective: The endoplasmic reticulum stress (ERS) and ERS-related neuronal apoptosis contribute to the cerebral ischemia/reperfusion (I/R) injury. (-)-Clausenamide has been reported to be nootropic and improve learning and memory in amnesia animal models. However, whether (-)-Clau could protect neurons from ischemic injury and the possible mechanism needed further study. The present study aimed to explore the effects of (-)-Clau on primary cortical neurons treated with oxygen-glucose deprivation/reoxygenation (OGD/R). Methods: Rat primary cortical neurons were used to set up an injury model of OGD/R which imitated the clinical I/R injury. Cell viability and apoptosis were measured by CCK-8 assay, LDH detection and TUNEL staining, respectively. The activation of GRP78/eIF2α-ATF4-CHOP signaling pathway, one of the three branches of ERS, and cleaved caspase-3, the apoptotic marker, were assessed by western blotting. Results: OGD/R induced activation of GRP78/eIF2α-ATF4-CHOP signaling pathway. (-)-Clau significantly attenuated OGD/R-induced decrease in the cellular viability and the activation of GRP78, eIF2α, ATF4 and CHOP. To further confirm the effect of (-)-Clau on OGD/R-induced ERS activation, the ERS inducer Tunicamycin (TM) was applied. TM significantly abolished (-)-Clau's protective effect against ERS and neuronal apoptosis, indicating that the protective effect of (-)-Clau was dependent on inhibiting ERS. Conclusions: The present work demonstrated for the first time that (-)-Clau could reverse the activation of GRP78/eIF2α-ATF4-CHOP branch, thus inhibited ERS and the subsequent apoptosis induced by OGD/R and promoted cell viability in vitro. (-)-Clau could serve as a promising therapeutic agent in the treatment for ischemic stroke in the future. Abbreviations: ATF4: activating transcription factor-4; ATF6: activating transcription factor-6; CHOP: transcriptional induction of CCAAT/enhancer binding protein homologous protein; (-)-Clau: 3-hydroxy-4-phenyl-5a-hydroxybenzylN-methyl-g-lactam; eIF2α: eukaryotic initiation factor 2α; ER: endoplasmic reticulum; ERS: endoplasmic reticulum stress; GRP78: 78-kDa glucose regulated protein; I/R: ischemia/reperfusion; IRE1: inositol requiring enzyme-1; JNK: c-Jun N-terminal kinase; OGD/R: oxygen-glucose deprivation/reoxygenation; PERK: double-stranded RNA-dependent protein kinase-like ER kinase; TM: Tunicamycin; UPR: unfolded protein response